2022
DOI: 10.1021/acs.jafc.2c01416
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation Mechanism of Flavan-3-ols by an Enzymatic Reaction Using Liquid Chromatography–Mass Spectrometry-Based Metabolomics Combined with Captured o-Quinone Intermediates of Flavan-3-ols by o-Phenylenediamine

Abstract: During the enzymatic oxidation of black tea, flavan-3-ols undergo a complicated chemical transformation and generate theaflavins and thearubigins. So far, the oxidation mechanism of flavan-3-ols has not been clarified. Liquid chromatography–tandem mass spectrometry-based metabolomics combined with o-quinone intermediates captured by o-phenylenediamine was developed and successfully applied in the liquid incubation of fresh tea homogenates. During the oxidation, the contents of catechins continuously decreased,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…It has also been reported that flavan-3ols found in tea plants, which are characterized by their meta-5,7-dihydroxy-substituted A-ring and catechol or pyrogallol B-ring, can easily be oxidized. This mechanism was studied in great detail [174]. The auto-oxidation of catechins, catalyzed by the endogenous enzymes polyphenol oxidase and peroxidase, can take place even when the enzymes are inactivated or removed.…”
Section: Phenolic Antioxidants (Ao) and Their Role In Stress-coping S...mentioning
confidence: 99%
“…It has also been reported that flavan-3ols found in tea plants, which are characterized by their meta-5,7-dihydroxy-substituted A-ring and catechol or pyrogallol B-ring, can easily be oxidized. This mechanism was studied in great detail [174]. The auto-oxidation of catechins, catalyzed by the endogenous enzymes polyphenol oxidase and peroxidase, can take place even when the enzymes are inactivated or removed.…”
Section: Phenolic Antioxidants (Ao) and Their Role In Stress-coping S...mentioning
confidence: 99%
“…Black tea, being the most consumed type of tea in the world, accounts for 80% of the global tea consumption (Kusano et al., 2015; Zha et al., 2022). Theaflavins (TFs), as the primary components of black tea, play a crucial role in the grade and quality of black tea, determining its color, brightness, strength, and briskness (Samanta et al., 2015).…”
Section: Introductionmentioning
confidence: 99%